PHYTOSOCIOLOGICAL CHARACTERIZATION OF WEEDS AS A FUNCTION OF RESIDUAL HERBICIDES APPLIED TO RICE GROWN UNDER SPRINKLER IRRIGATION. (27th February 2017) - CONCENÇO, G.; ANDRES, A.; TELÓ, G. M.; MARTINS, M. B.; MOISINHO, I. S.
SUMMARY: We aimed to characterize the weed community in sprinkler irrigated rice, previously applied with residual herbicides for two years, as well as to infer about sustainability of the management applied to the fields based on an ecological approach. The experiment was conducted during the cropping seasons 2013/14 and 2014/15, under sprinkler irrigation. Rice was planted in the second-half of October, using the cultivar PUITA INTA CL. Herbicides were applied in pre- and post-emergence (sequential application) of crop and weeds. Ryegrass ( Lolium multiflorum ) was planted in winter. In May 2015, soil samples were collected for the soil seed bank study. Phytosociological characterization of weeds emerged from the seed bank was conducted from May 2015 to January 2016, until soil seed bank depletion. Echinochloa crusgalli, Fimbristyllis sp., Cyperus esculentus and Killinga brevifolia were the weeds to which most concern should be directed when growing rice under sprinkler irrigation in lowland areas of Southern Brazil. Their competition strategies are based on density. Herbicides used should be efficient in controlling at least these four weed species. A selecting action of herbicides on weed species was botanically characterized, as the weed species reported after two cropping seasons depended on the herbicide treatment applied.